Dr. Jekyll and Mr. Hyde - Stevenson, Robert Louis, 1850-1894.; Yamamoto, Mitsu; Pablo Marcos Studio (New York Baronet Books, 2002)
A kind and well-respected doctor is transformed into a murderous madman by taking a secret drug of his own creation.
Originally published: New York : Playmore : Waldman Pub., 1990.
Accelerated Reader AR
Keywords: Horror stories